2015
DOI: 10.1021/jp512077m
|View full text |Cite
|
Sign up to set email alerts
|

Superior Photovoltaic Properties of Lead Halide Perovskites: Insights from First-Principles Theory

Abstract: Organic-inorganic methylammounium lead halide perovskites have recently emerged as promising solar photovoltaic absorbers. In this feature article, we review our theoretical understanding of the superior photovoltaic properties, such as the extremely high optical absorption coefficient and very long carrier diffusion length of CH 3 NH 3 PbI 3 perovskites through first-principles theory. We elucidate that the superior photovoltaic properties are attributed to the combination of direct band gap p-p transitions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
279
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(290 citation statements)
references
References 74 publications
10
279
1
Order By: Relevance
“…47 By investigating the trap states that could be formed by all possible intrinsic point defects in CH3NH3PbI3, it was found that Pb vacancies can pull up the valence band and Pb interstitials can pull down the conduction band, which would finally result in a narrower band gap. [48][49][50] Experimental results showed hole traps at the surface of CH3NH3PbI3 thin films and excitonic traps below the optical gaps in these materials, which are likely caused by electron-phonon coupling, especially at surfaces/interfaces of crystalline perovskites. 51 The electron paramagnetic resonance (EPR) studies also showed that in perovskites organic cations that deprotonate from their oxidized state, Pb 2+ cations as Pb 3+ centers trap holes while Pb 2+ cation clusters trap electrons.…”
Section: Trap States In Methylammonium Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…47 By investigating the trap states that could be formed by all possible intrinsic point defects in CH3NH3PbI3, it was found that Pb vacancies can pull up the valence band and Pb interstitials can pull down the conduction band, which would finally result in a narrower band gap. [48][49][50] Experimental results showed hole traps at the surface of CH3NH3PbI3 thin films and excitonic traps below the optical gaps in these materials, which are likely caused by electron-phonon coupling, especially at surfaces/interfaces of crystalline perovskites. 51 The electron paramagnetic resonance (EPR) studies also showed that in perovskites organic cations that deprotonate from their oxidized state, Pb 2+ cations as Pb 3+ centers trap holes while Pb 2+ cation clusters trap electrons.…”
Section: Trap States In Methylammonium Leadmentioning
confidence: 99%
“…The formation of trap states in CH3NH3PbI3 has been investigated computationally [47][48][49][50] and experimentally. 15,51,52 Elemental defects derived from Frenkel defects, such as Pb, I, and CH3NH3 vacancies, form shallow levels near band edges, which play the role of unintentional doping sources.…”
Section: Trap States In Methylammonium Leadmentioning
confidence: 99%
“…In addition to the well-known properties of perovskites, a unique feature that makes perovskites so good for PV applications relies on the fact that the energy of many electronic defects is expected to be close to the continuum of states within the bands, hence not detrimental for performance 47 .…”
Section: Challenges and Opportunitymentioning
confidence: 99%
“…One of the first and maybe most prominent examples of such a selection metric proposed for computational materials screening is presented by Yu and Zunger in 2012 [37] and has been widely used to estimate efficiency limits in the last years [38][39][40][41][42][43][44][45][46][47][48][49]. In their paper, they proposed a "spectroscopic limited maximum efficiency" SLME selection metric that aims to calculate efficiency limits for non-step like absorption coefficients beyond the radiative limit.…”
Section: Introductionmentioning
confidence: 99%